A case report of multi-step management of extracranial carotid artery aneurysm and carotid-cavernous fistula combination in patients - Nurimanov, Chingiz; Makhambetov, Yerbol; Kaliyev, Assylbek; Akshulakov, Serik (Frontiers in Neurology, 2023)
Extracranial carotid artery aneurysms (ECAA) and carotid-cavernous fistulas (CCF) are rare arterial pathologies with severe complications and increased risk of mortality. The optimal treatment approach for this combined condition is a topic of debate among neurosurgeons and neuroradiologists, and a standardized treatment protocol has yet to be established. The aim of this case report was to demonstrate the management of a rare combination of ECAA and CCF in patients. The treatment strategy included a two-step procedure of endovascular embolization of CCF followed by dual antiplatelet therapy and endovascular stenting of an aneurysm. Control angiograms showed the exclusion of an aneurysm from the blood circulation and CCF symptoms were resolved.